2018
DOI: 10.1002/aenm.201703155
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Pseudocapacitive Effect and Fast Ion Diffusion in Bimetallic Sulfides as an Advanced Sodium‐Ion Battery Anode

Abstract: Sodium‐ion batteries (SIBs) are promising next‐generation alternatives due to the low cost and abundance of sodium sources. Yet developmental electrodes in SIBs such as transition metal sulfides have huge volume expansion, sluggish Na+ diffusion kinetics, and poor electrical conductivity. Here bimetallic sulfide (Co9S8/ZnS) nanocrystals embedded in hollow nitrogen‐doped carbon nanosheets are demonstrated with a high sodium diffusion coefficient, pseudocapacitive effect, and excellent reversibility. Such a uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
267
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 403 publications
(273 citation statements)
references
References 61 publications
6
267
0
Order By: Relevance
“…As shown in Figure 7b, contrary to the EIS pattern, the PC and CS samples have the maximum and minimum slope values, respectively, so the composite of pure cobalt sulfide and porous carbon has a moderate slope, which means a lager lithium ions diffusion coefficient. This outcome is consistent with the GITT test, which was performed to elucidate the effect of multi‐step lithiation/delithiation on ion diffusion and conductivity properties 61. The corresponding diffusion coefficients at different discharge/charge voltages were calculated according to Equation (S2) (see details in the Supporting Information), and the results of the first two laps are shown in Figure 7c.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…As shown in Figure 7b, contrary to the EIS pattern, the PC and CS samples have the maximum and minimum slope values, respectively, so the composite of pure cobalt sulfide and porous carbon has a moderate slope, which means a lager lithium ions diffusion coefficient. This outcome is consistent with the GITT test, which was performed to elucidate the effect of multi‐step lithiation/delithiation on ion diffusion and conductivity properties 61. The corresponding diffusion coefficients at different discharge/charge voltages were calculated according to Equation (S2) (see details in the Supporting Information), and the results of the first two laps are shown in Figure 7c.…”
Section: Resultssupporting
confidence: 77%
“…The value of b varies from 0.5 (diffusion‐controlled process) to 1.0 (capacitive‐controlled process) and is calculated by the slope of log ( I ) versus log ( v ) plot (Figure 6b) 59. And the b values for peaks 1 and 2 are 0.72 and 0.74, respectively, indicating surface capacitive‐controlled process kinetically favored the CS@PC electrode 60, 61. According to Equation (3), by plotting I ( V )/ v 1/2 versus v 1/2 at different potentials, one can calculate the values of k 1 (slope) and k 2 (intercept) from the straight lines.…”
Section: Resultsmentioning
confidence: 99%
“…The difference was more obvious in the higher voltage range than in the lower range, which implied the better kinetic property of BT/C NFs . The calculated Na + diffusion kinetics ( D Na + ) during the discharge process were clearly presented in Figure S11c (Supporting information), and the calculation could be found in Figure S11b (Supporting information) . Both electrodes showed a progressively decreasing D Na + with the sodiation proceeding, which was associated with the sloping characteristics of the discharge profiles.…”
Section: Resultsmentioning
confidence: 90%
“…In addition, the biphasic material may contribute to high electronic conductivity and pseudocapacitive effect, leading to the fast ion diffusion kinetics. Moreover, the biphasic material with stepwise redox reactions can effectively reduce the solid‐state diffusion and thus relieve the stress during the insertion of ions . Remarkably, many zinc vanadates were demonstrated to exhibit superior electrochemical behavior as aqueous ZIB cathodes, especially the Zn 0.25 V 2 O 5 · n H 2 O material reported by Nazar and co‐workers, whose study revealed that Zn 0.25 V 2 O 5 · n H 2 O can perform at a high capacity and demonstrate excellent long‐term cyclic stability in virtue of its favorable structure.…”
Section: Resultsmentioning
confidence: 99%